(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The rice husk was characterized by proximate and ultimate analysis. The proximate analysis was determined by moisture, volatile and ash content as 15.48%, 57.28% and 15.35% respectively. Ultimate analysis was determined using the data obtained from proximate analysis to calculate carbon, hydrogen, nitrogen and oxygen percentage as 43.67%, 4.64%, 0.956% and 35.78% respectively. The rice husk pyrolysis was studied by TGA/DTG analysis in a nitrogen atmosphere at flow rate of 60mL/minute, heating from 20.00 oC to 1000.00 oC at three different heating rates: 10, 15 and 20 oC/minute. The devolatilization and decomposition pattern portray by TGA curve for all the samples were almost the same, however, different peak temperatures were shown by DTG curve differently for all the samples at different heating rates. The sample RHC ran at three different heating rates: 10, 15 and 20 oC/minute with peak temperatures of 260.85 oC, 318.14 oC and 358.57 oC respectively. While the acid modified samples RHL and RAA at the same heating rates of 10, 15 and 20 oC/minute with peak temperatures of 402.05 oC, 343.91 oC and 280.76 oC respectively for sample RHL. And 399.34 oC, 325.59 oC and 282.61 oC respectively for sample RAA. Three kinetic models were used in this research, which are known as model fit methods for kinetics. The models are Flynn Wall Ozawa (FWO), Kissinger Akahira Sunose (KAS) and Coats Redfern methods. The KAS and FWO methods were used for the determination of activation energy and C-R method for the reaction mechanisms